2010
DOI: 10.1111/j.1365-2648.2010.05470.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving insight into delusions: a pilot study of metacognitive training for patients with schizophrenia

Abstract: Metacognitive training appears to be a promising new technology which requires further research. It can be easily used by nurses to help patients with delusions to take into account their cognitive biases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 15 publications
2
25
0
1
Order By: Relevance
“…As a result, MCT did not prove to be cost-effective. Similar to other uncontrolled findings (Ferwerda et al 2010;Favrod et al 2011), we found small to medium within-subject effect sizes on symptom reduction in the experimental group (Cohen's d ranging from 0.29 to 0.64). The control group improved even further, reflecting a strong time effect.…”
Section: Discussionsupporting
confidence: 91%
“…As a result, MCT did not prove to be cost-effective. Similar to other uncontrolled findings (Ferwerda et al 2010;Favrod et al 2011), we found small to medium within-subject effect sizes on symptom reduction in the experimental group (Cohen's d ranging from 0.29 to 0.64). The control group improved even further, reflecting a strong time effect.…”
Section: Discussionsupporting
confidence: 91%
“…In line with the rationale of the training, most studies 30,32,[34][35][36][37] converge on the conclusion that MCT decreases delusion severity. A combination of MCT with social cognition training 38 showed significant positive effects on theory of mind, social perception, emotion recognition, and social functioning.…”
Section: -33mentioning
confidence: 67%
“…Evidence for such metacognitive problems led to the emergence of metacognitiveoriented psychological therapies (Briki et al, 2014;Favrod, Maire, Bardy, Pernier, & Bonsack, 2011;Moritz et al, 2013;Morrison et al, 2014). CIRCuiTS (Computerized Interactive Remediation of Cognition Training for Schizophrenia; Reeder et al, 2015) is a CR program explicitly promoting metacognitive components by including strategy use and guided practice, whilst retaining the role of the therapist in supporting and targeting metacognitive processing.…”
Section: Introductionmentioning
confidence: 99%